Therapeutic Hypothermia for Refractory Status Epilepticus - Zeiler, Frederick A.; Zeiler, Kaitlin J.; Teitelbaum, Jeanne; Gillman, Lawrence M.; West, Michael (Canadian journal of neurological sciences, 2015)
Background : Our goal was to perform a systematic review of the literature on the use of therapeutic hypothermia for refractory status epilepticus (RSE) and its impact on seizure control. Methods: All articles from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to May 2014), reference lists of relevant articles, and gray literature were searched. The strength of evidence was adjudicated by two independent reviewers, using both the Oxford and GRADE methodology. Results: Overall, 13 studies were identified, with 10 manuscripts and 3 meeting abstracts. A total of 40 patients were treated. The common target temperature was 33 degrees Celsius, sustained for a median 48 hours. Patients displayed a 62.5%, 15% and 22.5% rate of seizure cessation, seizure reduction, and failure of treatment respectively. External cooling was utilized in the majority of cases. Deep venous thrombosis, coagulopathy and infections were the commonly reported complications. Two ongoing clinical trials were identified. Conclusions: Oxford level 4, GRADE D evidence exists to support the use of therapeutic hypothermia to control seizures in RSE. Further prospective study is warranted. Hypothermie thérapeutique dans l’état de mal épileptique réfractaire. Contexte: Le but de cette étude était d’effectuer une revue systématique de la littérature au sujet de l’utilisation de l’hypothermie thérapeutique comme traitement de l’état de mal épileptique réfractaire (MER) et son impact sur le contrôle des convulsions. Méthode: Nous avons recherché les articles pertinents dans MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (du début à mai 2014), les listes de références des articles pertinents et la littérature grise. La puissance des données a été évaluée par deux reviseurs indépendants au moyen de la méthode d’Oxford et de la méthode GRADE. Résultats: Au total, 13 études ont été identifiées, dont 10 manuscrits et 3 résumés de présentations à des congrès. En tout, 40 patients ont été traités ainsi. La température cible générale était de 33° Celsius, maintenue pendant une médiane de 48 heures. L’hypothermie a induit un arrêt de la crise chez 62,5% des patients, une diminution des convulsions chez 15% et s’est soldée par un échec chez 22,5% des patients. Dans la majorité des cas, le refroidissement externe a été utilisé. Les complications les plus fréquemment rapportées étaient la thrombose veineuse profonde, la coagulopathie et l’infection. Deux études cliniques en cours ont été identifiées. Conclusions: Des données de grade 4 d’Oxford, de niveau D, existent en faveur de l’utilisation de l’hypothermie thérapeutique pour contrôler les crises dans le MER. Il est justifié de procéder à des études prospectives sur ce mode de traitement.